Character Education Model in Islamic Religious Education in Public High Schools in the City of Mataram - Dwiyani, Aryanti; Fadli, Adi; Jumarim, Jumarim; Fitriani, Muh. Iwan; Fuadi, Abdullah; Yorman, Yorman (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Character education is a value education that emphasizes moral or ethical aspects. The term character is known as morals which not only emphasizes moral knowledge (moral knowing/learning to know), but also moral formation (moral feeling/moral loving) and application or actualization of values (moral action/moral doing). Purpose. The purpose of this study is to describe the types of Islamic religious education activities that become a medium for strengthening character, forms of character that are strengthened through Islamic religious education activities and models of strengthening character values through Islamic religious education for students in public high schools in Mataram City. Method. This research is a qualitative research with data collection using observation, interviews and documentation. Data analysis uses the Miles and Huberman model starting from data collection, data condensation, data presentation and conclusions. Data validity was carried out with observation persistence, extension of participation, reference and triangulation. Results. The results showed that the model of strengthening character values through Islamic religious education at school was carried out through three process/stage models, namely: a) Knowledge of morals, b) Moral formation, c) Application or moral actualization which emphasizes the actualization of character values both in the school environment and in the wider environment. Conclusion. he character education model in this school is carried out with two models, namely the hidden curriculum model and the integration model.